The paradoxical relationship between fantasy football and NFL consumption: Conflict development and consumer coping mechanisms. Issue 2 (April 2017) - Yuksel, Mujde; McDonald, Mark A.; Milne, George R.; Darmody, Aron
Highlights: We examine the paradoxical relationship between fantasy football and NFL consumption. We apply grounded theory to utilize the viewpoint of fantasy football participants. We depict how a conflict between fantasy and NFL team may emerge. We present four coping strategies with conflicts on player selection. We also present four coping strategies with conflicts on rooting interests. We discuss these findings in terms of sport marketing theory and practice. Abstract: Fantasy sport participation represents an increasingly popular consumer experience among the contemporary sport consumption alternatives. Previous work on fantasy sports draws attention to both its positive and negative effects on traditional sport consumption. This study investigates fantasy football participants' perspectives, meanings, and experiences regarding their fantasy football and NFL consumption behavior. Employing a grounded theory methodology, the study draws on literatures spanning from sport consumption and fantasy sports to consumer co-creation and intrapersonal conflict, and combines them with data collection and analysis. The outcome is a new organizing framework that illustrates why there is conflict between fantasy and favorite team fandom and how fantasy sport participants cope with this conflict. First, the study illustrates that this conflict stems from the non-traditional co-creation opportunities inherent in the empowering fantasy sports experience, which leads to a psychological connection to the fantasy team and players through the feeling of self-achievement. Second, the study identifies various coping strategies that sport consumers employ to manage conflicts with player selection (i.e., safe selection, convergent selection, divergent selection, and impartial selection strategies) and rooting interests (i.e., balanced interest, principal interest-shift, temporal interest-shift, and benefit-seeking interest-shift strategies).